2021
DOI: 10.1007/s40519-021-01234-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the optimal male cut-off point: confirmatory factor analysis of the eating disorder examination-questionnaire (EDE-Q) in a representative sample of Spanish university students

Abstract: Purpose Although the EDE-Q is derived from the "gold standard" for the assessment of Eating Disorders (ED), its factor structure is controversial, particularly in male samples. The aim of the study was to examine the psychometric properties and factor structure of the EDE-Q, as well to stablish a sensitive and speci c cut-off point validated by EDE clinical interview.Methods A series of Con rmatory Factor Analyses were performed among a representative sample of 796 male university students, of whom 139 were in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Studies reveal that men with EDs, compared to women, are often less concerned with thinness [ 22 , 23 , 24 ], seek to increase body mass and muscularity instead [ 25 , 26 ], and may also present with different patterns in emotion regulation [ 27 ]. Given that established assessment tools rarely address men-associated ED symptoms, recent developments include men-oriented norms and extensions for established ED questionnaires [ 28 , 29 , 30 ] as well as men-specific assessment instruments [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveal that men with EDs, compared to women, are often less concerned with thinness [ 22 , 23 , 24 ], seek to increase body mass and muscularity instead [ 25 , 26 ], and may also present with different patterns in emotion regulation [ 27 ]. Given that established assessment tools rarely address men-associated ED symptoms, recent developments include men-oriented norms and extensions for established ED questionnaires [ 28 , 29 , 30 ] as well as men-specific assessment instruments [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the original version of the EDE-Q scored item 8 on both the WC and the SC subscale. This within-item-multidimensionality caused estimation problems in our analyses (not positive definite covariance matrix), so that we assigned this item to WC only (the same problem has been reported Rica et al, 2022 , for example). Even assigning item 8 only to the WC or the SC subscale (because the item addresses both weight and shape concerns), respectively, still yielded a not positive definite covariance matrix.…”
Section: Resultsmentioning
confidence: 92%
“…This is in line with prominent theories of body image (e.g., self-discrepancy theory, objectification theory; Cash, 2012 ; Vartanian, 2012 ). In addition, Penelo et al ( 2013 ) and Rica et al ( 2022 ) reported a 2-factorial structure (RS and EC+WC+SC). Moreover, in some analyses items were dropped from the final solution (see Rand-Giovannetti et al, 2020 Table 1 for an overview), so that no overarching latent structure is discernible for the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Eating Disorder Examination Questionnaire (EDE-Q; Fairburn and Beglin, 1994;Peláez-Fernández et al, 2012;Rica et al, 2021): The questionnaire has 28 items, that asks directly about attitudes related to key features of ED psychopathology in a 28-day time frame. The same four subscales (i.e., Restraint, Eating concern, Weight concern and Shape concern), of the EDE interview are calculated through 22 attitudinal items, and responses are given on a 7-point Likert-type scale from 0 (never) to 6 (every day).…”
Section: Methodsmentioning
confidence: 99%